Radiometric activities of sediment cores from the northern Barents Sea - Thaise Ricardo de Freitas; Silvia Hess; Paul E Renaud; Peter G Appleby; Elisabeth Alve (PANGAEA, 2025)
Sediment cores (40 cm long, 10 cm diameter) were retrieved at nine stations (NPAL04 to NPAL19) with a four-tube multi-corer. Additionally, one short sediment core (6 cm length x 5 cm diameter) was subsampled from a giant box corer deployment at station P1. All sediment cores were immediately sliced into 1 cm layers, and subsamples were directly frozen on board ( 20 °C). Radiometric activities (210Pb, 226Ra, and 137Cs) were analysed by direct gamma assay in the Environmental Radioactivity Laboratory at the University of Liverpool. Supported 210Pb activity (210Pbsup) was assumed equal to the measured 226Ra activity in the sediments. Excess 210Pb activity (210Pbxs) was calculated by subtracting 210Pbsup from the measured total 210Pb activity (210Pbtotal).
In: Ricardo de Freitas, T et al. (2025): Sedimentary and geochemical properties of sediment cores from the northern Barents Sea [dataset bundled publication]. PANGAEA, https://doi.org/10.1594/PANGAEA.986961